CONECTOR DE CISALHAMENTO EM PERFIL FORMADO A FRIO: ANÁLISE VIA MODELAGEM COMPUTACIONAL - SILVA, Paulo Henrique Menezes (2006)
In a composite system, a steel beam (laminated, welded or cold formed) is associated with a concrete slab, forming a composite beam. The interaction between concrete and steel can be mechanical, by friction or, in some cases, only by adherence. One of the major advantages of the composite beams is the increase in strength and stiffness due to association of steel and concrete that makes possible the reduction of the height of the structural elements, implicating in material economy. The present research has the purpose to present a general vision of the structural behavior of the composite steel-concrete beams and to proceed to a more detailed study of the behavior of the shear connectors made from cold formed steel. A modeling study of the push-out test is accomplished with the intention to find the factors that influences the resistance and rigidity of the connection. The numerical study consists in the elaboration of a three-dimensional numerical model to simulate the push-out test from which is obtained the force-displacement curve, ultimate load, deformations and tensions along the connector. The numeric results are compared with obtained experimental values of rehearsals accomplished at laboratory for validation of the same ones. For the accomplishment of the numeric modeling the computational program ANSYS® 6.1 was used, which uses non-linear material and geometric Finite Element Method models. The numeric models present as variables of interest the thickness, the height of the shear connectors made of cold formed steel and the resistance of the concrete used in the premolded slab with reinforced concrete lattice joist. Results showed that the thickness of the connector is the most important variable in the connection strength, however the height of the connector also has influence in the resistance and, mainly, in the rigidity of the connection.